Correlation between wrist circumference with blood pressure and creatinine level among elderly - Etisa Adi Murbawani; Etika Ratna Noer; Enny Probosari (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: Hypertension is a highly prevalent health problem which incidence is greatest among the elderly. Hypertension may increase creatinine level and leads to other health problems like diabetes mellitus, kidney damage, and cardiovascular disease. Wrist circumference is a simple anthropometric measurement that can be used to identify hypertension and increasing level of serum creatinine.Objectives: To analyze the correlation of wrist circumference with blood pressure and creatinine level among the elderly.Materials and Methods: This was a cross-sectional study with a purposive sampling method. Subjects of this study were 84 women aged 60 years old or above at Unit Rehabilitasi Sosial Pucang Gading Semarang. The independent variable of this study was wrist circumference, and the dependent variables were systolic blood pressure, diastolic blood pressure, and creatinine level. The result was analyzed using the Spearman-rho test.Results: The participants of this research were 49% women aged 60-65 years old, with an average age was 65.5 years old. The prevalence of hypertension was 61.9%. Most hypertension incidence in this research was caused by high systolic blood pressure (50%), and the rest was caused by high diastolic blood pressure (3.9%) and both (46.1%). The level of creatinine was normal with an average level was 0.75 mg/dL. There was no correlation of wrist circumference with systolic blood pressure systolic (r=0.15; p=0.19), diastolic blood pressure (r=0.1; p=0.38), and creatinine serum (r=0.18; p=0.09) among elderly.Conclusions: There was no correlation of wrist circumference with blood pressure and creatinine level among the elderly.